Structural, dielectric and magnetic properties of xNi0.50Zn0.40Mn0.10Fe2O4 + (1-x)Bi0.90La0.10Fe0.93Eu0.07O3 multiferroic composites. (26th April 2021) - Kaiyum, A; Hossain, M A; Momin, A A; Rashid, R; Alam, F; Hakim, M A; Khan, M N I
Abstract: Multiferroic composites with chemical formula x Ni0.50 Zn0.40 Mn0.10 Fe2 O4 + (1- x )Bi0.90 La0.10 Fe0.93 Eu0.07 O3 were prepared by solid state reaction technique. These composites are a mixture of ferrite and ferroelectric phases confirmed by X-ray diffraction (XRD). The phases are crystalline in nature as concentrated and strident peaks were observed in XRD patterns. Elongating and twisting ambiences of various bonds are existing in the composites which are observed from FTIR studies. The surface morphology of the prepared samples was studied by Field Emission Scanning Electron Microscope and detected that materials are dense but there is inhomogeneity in grain size distribution. It was established by the Energy Dispersive X-ray Spectroscopy that all the elements existing in the composition were at an appropriate ratio. The magnetic hysteresis loops of the composite materials were investigated by using Physical Property Measurement System at room temperature. Magnetic properties have been enhanced significantly due to the assimilation of NZMFO in the composites. To understand the ferroelectric strength of the composites, electrical properties of the composite material were studied by P-E hysteresis loop analyses in an external electric field. From P-E hysteresis loops it is observed that the 0.2Ni0.50 Zn0.40 Mn0.10 Fe2 O4 + 0.8Bi0.90 La0.10 Fe0.93 Eu0.07 O3 composite have shown better ferroelectric nature. Dielectric constant decreases with the increase of ferrite content. The ac resistivity was to be decreased with ferrite content which indicates the reduction of eddy current loss with the increase of ferrite content. The maximum value of α ME (178 × 10 3 Vm −1 T −1 ) is found for 0.2NZMFO + 0.8BLFEO composite.